Implementasi Supervisi Akademik Kepala Madrasah dalam Meningkatkan Profesionalisme Guru di MTs Zainul Hasan Genggong Pajarakan Probolinggo - Abdul Hamid (LP3M Universitas Islam Zainul Hasan Genggong, 2016)
The essence of education at the school is a learning process. There is no quality of education in schools without the equal of learning quality. Various efforts to improve the quality of education in schools can be perceived as less useful if it is not touched the improvement of the learning process. Among all components of learning, the teacher is the crucial one. There is no quality of learning without the equal quality of the teachers. One of the programs held in order to empower teachers is an academic supervision. It is a series of activities to help teachers in developing their ability to manage the learning process for the achievement of academic goals. Thus, the essence of academic supervision is to help teachers in developing skills professionalism. In achieving that lofty goal, the academic supervision should be implemented in all scope of the school. Moreover, the implementation of it is done by the principal as a leader, and as well as a supervisor who can foster the good morale for teachers. Based on the mentioned background, the researcher conducts the research on the implementation of the principal academic supervision in improving teachers’ professionalism in MTs Zainul Hasan Genggong Pajarakan Probolinggo. The purpose of the study is to describe the planning of the principal academic supervision in improving teachers’ professionalism, to describe the implementation of the principal academic supervision in improving the teachers’ professionalism, and to describe the evaluation of the principal academic supervision in improving the professionalism of teachers. This study uses qualitative research methods, and the explanation of the research results are not numerical but scientific one. The effort to obtain the valid data, the selected samples taken in this study by using purposive sampling techniques to select those that are considered most competent to understand the examined object. The data collection method uses observation, interviews, and documentaries. The observation methods are done by observing and recording, the interviews are conducted by interviewing the informants, and documentation methods are made to the objects documented. The data obtained are analyzed by using descriptive qualitative data analysis techniques, and then the validity of the data is applied by using triangulation techniques. Based on the results of the study, the implementation of principal academic supervision in improving the teachers’ professionalism in MTs Zainul Hasan Genggong Pajarakan Probolinggo is concluded as follow: First, the planning of academic supervision program is organized at the beginning of the school year before starting the overall teaching and learning activities, and included in the work program or the School Budget by involving all components of the school in determining the planning objectives, basic tools, and methods used in the academic supervision . Second, in implementing the academic supervision, the supervisor uses the individuals and groups techniques as well as the direct and indirect approaches. Third, in the results of the evaluation of academic supervision, it is found several obstacles, such as: (1) from the teachers point; the coaching process done by the principal are less as teachers often do not attend in the regular meetings as well as the meeting to implement the supervision models. (2) from the principal point; occasionally, the principal does not attend in the teachers coaching process that has been scheduled. (3) from the funds point; the lack of funds in in-service training activities caused by unbudgeted program arranged by the agency so that the teacher got less information due to the implementation done regularly.